Genome-wide comparative analysis of photosynthetic enzymatic genes provides novel insights into foxtail millet and other cereals - Raturi, Arpit; Shekhar, Shivam; Jha, Ratnesh Kumar; Chauhan, Divya; Pandey, Saurabh; Kumari, Sarita; Singh, Ashutosh (Frontiers in Genetics, 2024)
C4 crops have more efficient photosynthetic pathways that enable their higher photosynthetic capacities as well as nitrogen and water use efficiencies than C3 crops. Previous research has demonstrated that the genomes of C3 species include and express every gene needed for the C4 photosynthesis pathway. However, very little is known about the dynamics and evolutionary history of such genetic evolution in C4 plants. In this study, the genes encoding five key photosynthetic pathway enzymes in the genomes of C3 (rice), C4 (maize, sorghum, and foxtail millet), and CAM (pineapple) crops were identified and compared systematically. The numbers of genes in these photosynthetic enzymes were highest in the C4 crops like sorghum and foxtail millet, while only eight genes were identified in the CAM plant. However, 16 genes were identified in the C3 crop rice. Furthermore, we performed physical, chemical, gene structure and, cis-element analyses to obtain complete insights into these key genes. Tissue-specific expressions showed that most of the photosynthetic genes are expressed in the leaf tissues. Comparisons of the expression characteristics confirmed that the expression patterns of non-photosynthetic gene copies were relatively conserved among the species, while the C4 gene copies in the C4 species acquired new tissue expression patterns during evolution. Additionally, multiple sequence features that could affect C4 gene expressions and subcellular localization were found in the coding and promoter regions. Our research also highlights the variations in how different genes have evolved within the C4 photosynthetic pathway, and we confirmed that specific high expressions in the leaves and right distribution within the cells were crucial for the development of the C4 photosynthetic abilities. The findings of this study are expected to aid in understanding the evolutionary process of the C4 photosynthetic pathway in grasses as well as offer insights for modifying the C4 photosynthetic pathways in wheat, rice, and other significant C3 cereal crops.